Masyarakat dan Eksistensi Madrasah Diniyah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
As a part of social structure, any educational institution is always changing depending on the social dynamic in a society. in the same manner, madrasah diniyah-as one of the religious educational institutions is also changing due to their environment and social aspiration. in this case, the madrasah existence seems to be depended on what and how social aspiration towards madrasah. madrasah is built and managed by society. social differences-because of difference in gender, age, level of education, and occupation-do not hinder the educational spirit of community to support madrasah diniyah. this paper tries to answer some questions dealing with their existence today. why the community still wants to conserve the existence of madrasah diniyah? how far the social aspiration to conserve and develop the madrasah diniyah as a tool of values cultivation.
Keywords: society; madrasah diniyah; social dynamic